2004
DOI: 10.1207/s15327914nc5001_3
|View full text |Cite
|
Sign up to set email alerts
|

Eating Frequency and Colon Cancer Risk

Abstract: Increased exposure of the colon to bile acids, as a result of increased eating frequency, might promote the development of colon cancer. Our aim was to evaluate the association between eating frequency and colon cancer. We used data from a population-based case-control study of colon cancer in North Carolina. Eating frequency (a combination of meals and snacks) was categorized as fewer than three, three or four, or more than four eating episodes per day. Multivariate logistic regression was used to calculate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…These compounds, especially β-carotenes, are capable of binding and eliminating free radicals, and repairing DNA damage, inhibiting cell proliferation, inducing apoptosis, and suppressing angiogenesis [ 89 ]. Flavonoids have been acknowledged to have a role in protecting against and preventing non-communicable diseases [ 90 , 91 , 92 , 93 ], and neoplasms in particular, due to their potent antioxidant and DNA repairing activity. In this review, the dietary impact of various subclasses of flavonoids was analyzed, and it proved significant for flavonols, flavones, and flavan-3-ol swell classes, particularly after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds, especially β-carotenes, are capable of binding and eliminating free radicals, and repairing DNA damage, inhibiting cell proliferation, inducing apoptosis, and suppressing angiogenesis [ 89 ]. Flavonoids have been acknowledged to have a role in protecting against and preventing non-communicable diseases [ 90 , 91 , 92 , 93 ], and neoplasms in particular, due to their potent antioxidant and DNA repairing activity. In this review, the dietary impact of various subclasses of flavonoids was analyzed, and it proved significant for flavonols, flavones, and flavan-3-ol swell classes, particularly after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, hyperinsulinemia is associated with increased cardiovascular, coronary, and all-cause mortality, independent of other risk factors [61]. Interestingly, “snacking” has also been linked to increased risk of type 2 diabetes [62] and cancer [63]. …”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous case-control studies have observed a positive relationship between eating frequency and CRC (3, 4, 1620, 22, 23). However, the case-control design is subject to recall bias, and it is possible that diagnosis or symptoms influenced actual eating behavior or recall of eating frequency in cases in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overall glycemic effect and quantity of carbohydrates consumed, as reflected by the dietary glycemic load (GL) is positively associated with risk for CRC (13), and dietary GL may modify the association between eating frequency and CRC via its influence on concentrations of blood glucose and insulin (14, 15). Although the majority of case-control studies have suggested a positive relationship between eating frequency and risk for CRC (3, 4, 1623), only a few prospective cohort studies have been published. Tseng et al examined data from NHANES and reported a borderline-significant inverse association between eating frequency with colorectal cancer risk (24).…”
Section: Introductionmentioning
confidence: 99%